2001
DOI: 10.1007/s004030100239
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of lipid peroxidation products, protein-bound acrolein and 4-hydroxynonenal protein adducts, in actinic elastosis of photodamaged skin

Abstract: Acrolein and 4-hydroxy-2-nonenal (HNE) are both byproducts of a lipid peroxidation reaction. Actinic elastosis in photodamaged skin of aged individuals is characterized by the accumulation of fragmented elastic fibers in the sun-exposed areas. To study whether a lipid peroxidation reaction is involved in the accumulation of altered elastic fibers in actinic elastosis, skin specimens obtained from sun-damaged areas were immunohistochemically examined using the antibodies against acrolein and HNE. Both antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 23 publications
3
62
1
1
Order By: Relevance
“…These two approaches may also be combined. with proteins was also developed and tested around the same time [102,103]; subsequently other researchers produced an antibody against the same immunogen, and showed that it recognized acrolein-modified albumin [104]. Using this antiserum they developed an ELISA and reported limited cross-reactivity with adducts of formaldehyde, malondialdehyde, or 4-hydroxynonenal with albumin.…”
Section: Analysis Of Free Aldehydic Oxidation Products and Their Metamentioning
confidence: 99%
“…These two approaches may also be combined. with proteins was also developed and tested around the same time [102,103]; subsequently other researchers produced an antibody against the same immunogen, and showed that it recognized acrolein-modified albumin [104]. Using this antiserum they developed an ELISA and reported limited cross-reactivity with adducts of formaldehyde, malondialdehyde, or 4-hydroxynonenal with albumin.…”
Section: Analysis Of Free Aldehydic Oxidation Products and Their Metamentioning
confidence: 99%
“…For example, nonfragmented OxPLs induce barrier-protective effects in lung endothelium, whereas fragmented species are barrier disruptive ( 9 ). Similarly, exposure of dermal fi broblasts to UVA-generated, nonfragmented oxidized phosphatidylcholine (OxPCs) induced adaptive responses ( 10,11 ), whereas production of fragmented species containing reactive carbonyl groups correlated to skin ageing ( 12 ) and pathologies of the skin that develop upon solar exposure, such as actinic elastosis ( 13 ).…”
Section: Irradiation Of Cellsmentioning
confidence: 99%
“…In addition, the damaged lung may "remember" the accumulated inflicted injury. For example, in damaged skin, colocalization of elastin and the oxidative stress marker 4-hydroxy-nonenal has been identified, as well as colocalization of elastin and the cell toxin acrolein (116). Although acrolein can upregulate endothelial cell heme oxygenase-1 (117), it is also one of the most chemically reactive aldehydes inhaled with cigarette smoke (118), and lysyl-acroleinated proteins have been detected in plasma samples from smokers (119).…”
Section: Can There Be Repair?mentioning
confidence: 99%